Hubungan Pengetahuan Dan Motivasi Pasien Hipertensi Terhadap Kepatuhan Berobat Di Puskesmas Limau Purut Padang Pariaman - Boy Andre; Yulia Fitriani; Vilma Humaira (Universitas Sumatera Barat, 2026)
Hypertension is a condition characterized by persistently elevated blood pressure with systolic pressure ≥140 mmHg or diastolic pressure ≥90 mmHg (WHO). Patient adherence to antihypertensive therapy is essential for controlling blood pressure and preventing complications, with knowledge and motivation playing key roles in treatment compliance. This study aimed to determine the relationship between knowledge and motivation of hypertensive patients and their medication adherence at Limau Purut Public Health Center, Padang Pariaman Regency, in 2024. This quantitative correlational study used a total sampling technique involving 84 respondents, and data were collected through guided questionnaires. The results showed that 38.1% of respondents had good knowledge and 48.8% had good motivation, while 61.9% had poor knowledge and 51.2% had low motivation. The percentage of patients adhering to treatment was 47.6%. Statistical analysis revealed a significant relationship between knowledge and medication adherence (p = 0.002; p < 0.05) and between motivation and adherence (p = 0.000; p < 0.05). These findings indicate that higher knowledge and motivation levels are associated with better adherence to hypertension therapy. Health workers are encouraged to provide educational materials, such as leaflets, to improve patients’ knowledge, motivation, and overall health outcomes.